(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The study aimed to analyze the current use of social media by Nama’a Charitable Society in terms of the platforms utilized, the types of content published, and the mechanisms for managing digital accounts, as well as to assess the effectiveness of social media in delivering the society’s programs and services to the targeted audience and to identify the challenges and obstacles faced by the society in using social media for charitable marketing. The study adopted a descriptive-analytical approach and included a sample of 134 individuals from the city of Jeddah who are familiar with and have knowledge of Nama’a Charitable Society’s activities. The study concluded that Nama’a Charitable Society has a strong and effective presence on social media, with a mean usage score of 4.16, indicating a high level of utilization of digital platforms to communicate with the public. The study also revealed that the society’s accounts are updated regularly and systematically, reflecting a clear interest in maintaining a continuous media presence. Furthermore, the results showed that Nama’a relies on diverse content (textual, visual, and audio), which contributes to higher engagement levels, and there is a strong correlation between social media use and the effectiveness of delivering the society’s programs and services.